Conceptual framework of sickness absence and return to work, focusing on both the individual and the contextual level. - Labriola M (Work, 2008)
AIM: The aim of this study is to give an overview of the individual and workplace level factors affecting sickness absence and return to work based on international literature. Categorizing the individual and workplace level factors in a conceptual framework encompasses both sickness absence and return to work. Testing the practical use of the conceptual framework 'The Dynamic Work Disability Model' in study design and interpretation of five studies in a Danish context. METHODS: The project features five prospective cohort studies focusing on associations between work environment and different sickness absence and return to work outcomes. These five studies utilize two different work environment cohorts and a national sickness absence register data. The following analyses were performed: Logistic, Cox, multilevel logistic and Poisson regressions. RESULTS: A research project on sickness absence and return to work designed according to the 'The Dynamic work Disability Model' contributed to an understanding of the proportions and basic epidemiology of work disability in a Danish labor market context. The use of 'The Dynamic Work Disability Model' helped in designing and structuring the research project's sub-studies and supported a more systematic interpretation of the findings.